Sustainable degradation of agricultural pesticides in real waters by graphene/CuFe2O4-driven heterogeneous solar photoelectro-Fenton process - dos Santos, Clécia Andrade [UNESP]; Santos, Thalles Henrique; de Souza Cruz, Daiane Requião; Rossini, Eduardo Luiz [UNESP]; Romão, Luciane Pimenta Cruz [UNESP]; Zanoni, Maria V. Boldrin [UNESP]; Salazar-González, Ricardo (Elsevier, 2025)
Agricultural pesticides are emerging contaminants of concern due to their persistence, toxicity, and widespread use in crop production. This study addresses the challenge of removing three commonly used insecticides: methomyl, carbendazim, and imidacloprid from water using a heterogeneous solar photoelectro-Fenton (HSPEF) process. A graphene/CuFe2O4 magnetic catalyst was synthesized and applied in combination with a boron-doped diamond (BDD) anode and an air diffusion cathode, under natural sunlight. The process was optimized at pH 9, with a current density of 33 mA cm−2 and catalyst dosage of 75 mg L−1. Under these conditions, complete degradation (100 %) of all three pesticides was achieved in synthetic solutions within 120 min. When applied to real water samples (secondary effluent and river water) fortified with 5 mg L−1 of each pesticide, removal efficiencies reached 100 % for methomyl, 71 % for carbendazim, and 56 % for imidacloprid. Total organic carbon (TOC) removal reached 40 %, and LC-MS/MS analysis confirmed the formation of transformation products with reduced predicted toxicity. The catalyst demonstrated good stability and reusability, with minimal leaching. These results highlight the potential of the HSPEF process as a sustainable and scalable technology for the treatment of pesticide-contaminated effluents, particularly under solar irradiation and alkaline pH, making it attractive for agricultural and decentralized water treatment applications.